Post Covid teaching and learning from students’ perspective - Damiri, Harlina; Baharuddin, Naemah; Usop @ Yusoff, Habibah; Mohd Noor, Adibah; Syed Hussain, Sharifah Fadzlon; Mohd Noor, Mazni (Centre of Foundation Studies, International Islamic University Malaysia, 2023)
A survey was carried out on the students from the Centre for Foundation Studies, International Islamic University Malaysia (CFS IIUM) in Semester 1 Session 2022/2023. These students had been going through the Remote Teaching and Learning (RTL) during pandemic in their first year of study and after the pandemic era they are currently undergoing face-to-face teaching and learning. In this study, questionnaires have been given to them and 101 responses were collected. This consists of 16.8 % arts and 83.2 % science-based background. The questionnaires have been developed by means of Google Form which covered the demography of the students and their experiences during RTL as well as face-to-face mode during post pandemic classes. The responses were measured by means of Likert’s scale and data has been extracted and analysed using Excel and IBM SPSS Statistics v26. The results of the survey were analysed using descriptive analysis. It was revealed that the students preferred face-to-face over online classes because they can learn effectively either using traditional white board and marker pen method or embedding online and technology assisted elements during classes. They also satisfied with having face-to face discussions with peers as well as having effective interaction and communication with lecturers. However, they agreed that the quality of their learning can be enhanced using the latest technology such as gamification and other online platforms. Giving them a choice, they prefer to have a combination of face-toface and online classes where 49.5% had chosen a 70:30 ratio of face-to-face over online mode. Therefore, lecturers of CFS IIUM should be ready and well equipped with state-of-the-art technology in teaching and learning to facilitate alternative methodology such as blended learning or hybrid mode whilst prioritizing face-to-face mode.